The Choice of Law Issues in Marine Insurance Disputes Resolution in Indonesia - Marnia Rani (Universitas Lampung, 2017)
Marine insurance business in Indonesia such as marine hull and machinery insurance and cargo insurance are subject to applicable laws and practices in the United Kingdom. Although Indonesia already has marine insurance law which is regulated in Wetboek van Koophandel, in fact, this business subject to English Law and Practice. The choice of law is listed in the insurance policy. Submission of the law and practice in the UK raises the issue for the parties in the insurance contract, between Insurer and Insured. Although the principle of the contract is a law for those who make it, in practice, there is a problem. The problem is especially when there is a dispute between Insurer and Insured. When disputes occur, each party has a different opinion regarding which country's laws may be applied to resolve disputes between Insurance Companies and Policyholders (the proper law of the contract, the applicable law). When referring to the provisions contained in the marine insurance policy which is a contract of the parties, it should be settled under the legal system and the practice of law which is in force in the United Kingdom, because the choice of law is written in the contract. However, the problem arises again, whether the choice of law in the insurance contract can be applied, if the insurance company as a legal entity is established under Indonesian law and domiciled in Indonesia, as well as the policyholders who are Indonesian. On the basis of such matters, this paper intended to elaborate the principles of international civil law in Indonesia regarding the choice of law in the contract and is also associated with the personal status of the insurance company, the personal status of the policyholder who are Indonesian, as well as the consequences of the choice of law listed in marine hull and machinery insurance or cargo insurance and national laws which can be applied to marine insurance disputes occurring in Indonesia. Keywords: Marine Insurance, Choice of Law